PENGUATAN PROFIL PELAJAR PANCASILA MELALUI EKSTRAKURIKULER PRAMUKA UNTUK PEMBENTUKAN KARAKTER GOTONG ROYONG PESERTA DIDIK DI SDN 36 PAYAKUMBUH - Syafutri, Rahmi Aulia; Waldi, Atri; Ladiva, Hasmai Bungsu; Mansurdin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe: (1) the implementation process of strengthening mutual cooperation character through Scout extracurricular activities at SDN 36 Payakumbuh, and (2) supporting and inhibiting factors in its effective implementation. This research uses a descriptive qualitative approach with subjects consisting of the school principal, classroom teachers, Scout leaders, and student guardians. Data collection techniques were carried out through interviews, observation, and documentation, with data analysis through the stages of data reduction, data presentation, and conclusion drawing. Data validity was strengthened through triangulation of sources and techniques. The results showed that Scout extracurricular activities become a strategic means in strengthening the Pancasila Student Profile, particularly in the dimension of mutual cooperation. Elements emphasized in the formation of mutual cooperation character include concern for others, ability to collaborate in groups, and an attitude of sharing and helping each other. Value points were also generated such as: Appreciation, Democracy, Tolerance, Empathy, Deliberation, Mutual assistance, Anti-discrimination, and Volunteerism. These values are instilled through the stages of planning, implementation, evaluation, and output in Scout activities. Activities such as flag ceremonies, class duty rotations, morning exercises, and Clean Friday also support the habituation of mutual cooperation character al school. Supporting factors for the implementation of these activities include the availability of adequate infrastructure and full support from parents. Meanwhile, inhibiting factors include weather constraints, limitations of learning media, financing, weak student management, and a suboptimal evaluation system.